Performance appraisal System an effective performance management system: Perceptions of employees at Mashwede Holdings. - Nyasha, Mapira (IJRDO - Journal of Applied Management Science, 2016)
The research sought to assess perceptions of employees on the effectiveness of performance appraisal as a performance management tool at Mashwede Holdings in Zimbabwe. The research was carried out in the form of a case study in which a sample of 52 employees from a population of 74 employees was used. Stratified random sampling procedure was employed in selecting elements from 6 managers and 46 general employees. Questionnaires and interviews were used in triangulation to collect data on the sample. After analyzing the collected data, it was found that performance appraisal assist in performance measurement. The study also found that the effectiveness of performance appraisal system is a cause of concern because of its shortfalls. The effectiveness of performance appraisal system has been hampered by various challenges such as halo effect, horn effect, stiffness, central tendency and personal bias. The study recommended that modern methods of performance appraisal be used and make use of contemporary performance management systems like Results Based Management (RBM) and Balance Score Card system (BSC).